Pengembangan Aplikasi Usaha Bimbingan Belajar Konsep STEM (Science, Technology, Enginerring & Mathematics) dengan Konten Kearifan Lokal Kalimantan Tengah - Helmi Helmi; Diplan Diplan; Muhammad Rezeki; Febria Helena; Putri Anggraini (Pusat Riset dan Inovasi Nasional, 2026)
This Community Service Program (PKM) aims to develop a tutoring application that integrates the STEM (Science, Technology, Engineering, and Mathematics) learning concept with the local wisdom of Central Kalimantan for the Super Class tutoring program in Pulang Pisau Regency. This initiative emerged in response to the need for innovative learning media that are culturally relevant, technologically supported, and can enhance students' understanding of STEM subjects while also strengthening their connection to regional identity. The application is equipped with interactive learning modules, contextual STEM problem-solving activities, and digital content that highlights local knowledge, such as traditional environmental practices, indigenous technologies, and regional cultural values. The program uses a participatory design approach, involving tutors, students, and local education stakeholders through needs assessments, focus group discussions, prototype development, and iterative testing. The implementation results show that this application increases student engagement, improves their understanding of STEM concepts, and facilitates more dynamic tutoring sessions. Furthermore, this digital platform enhances the operational capacity of the Super Class tutoring program by expanding service reach and supporting integrated learning modes. This PKM demonstrates that integrating STEM education with local wisdom through digital innovation can enrich the learning experience, support cultural preservation, and strengthen community-based education services in Pulang Pisau.